A Sensing Device with the Optical Temperature Sensors-Based Quad-RX Module and a Security Module - Kim, Kyeeun; Park, Siwoong; Yeo, Chanil; Park, Hyoung-Jun; Kim, Hyunjin; Heo, Young Soon; Kang, Hyun Seo; Kim, Kyungsoo (Sensors (Basel, Switzerland), 2021)
In this paper, we present a sensing device with the optical temperature sensors-based quad receiver (Quad-RX) module and a security module. In addition, in order to prevent cyberattacks on critical national infrastructures and key facilities, we implemented symmetric-key and secure hash algorithm-based hardware security modules in the key elements of the sensing device. A preliminary test was conducted prior to a field trial to verify the performance of the developed sensing device. The accuracy and stability of the sensing device were then verified for 1 month in a field test at facilities for energy storage systems and photovoltaic converters in sewage treatment plants.